2010
DOI: 10.1016/j.jhep.2010.01.041
|View full text |Cite
|
Sign up to set email alerts
|

HCV resistance to cyclosporin A does not correlate with a resistance of the NS5A–cyclophilin A interaction to cyclophilin inhibitors

Abstract: Background & Aims-The cyclophilin (Cyp) inhihibitors -cyclosporine A (CsA), NIM811, Debio 025 and SCY 635 -block HCV replication both in vitro and in vivo, and represent a novel class of potent anti-HCV agents. We and others showed that HCV relies on cyclophilin A (CypA) to replicate. We demonstrated that the hydrophobic pocket of CypA, where Cyp inhibitors bind, and which controls the isomerase activity of CypA, is critical for HCV replication. Recent studies showed that under Cyp inhibitor selection, mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
128
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(149 citation statements)
references
References 30 publications
20
128
1
Order By: Relevance
“…This is consistent with the fact that CypI have a unique MoA, which is the prevention of contacts between the host protein CypA and the viral protein NS5A [38,[43][44][45][46][47][51][52][53]. We showed that CypI such as ALV and SCY-635 block interactions between CypA and NS5A derived from various GTs [43][44].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with the fact that CypI have a unique MoA, which is the prevention of contacts between the host protein CypA and the viral protein NS5A [38,[43][44][45][46][47][51][52][53]. We showed that CypI such as ALV and SCY-635 block interactions between CypA and NS5A derived from various GTs [43][44].…”
Section: Discussionsupporting
confidence: 86%
“…Two mutations-D320E and Y321N -were identified in the NS5A region of the STG-175-resistant replicon colonies. The D320E and Y321N mutations have been previously identified in HCV variants resistant to other CypI including CsA, ALV, SCY-635 and NIM811 [43][44][45][46][47][48][49]. Thus, it is likely that the double E320/N321 substitutions represent a common motif of partial resistance to CypI including STG-175.…”
Section: Discussionmentioning
confidence: 95%
“…As a control, we used GSTCypA as bait to capture full-length NS5A-His because this interaction has been shown to be direct (15)(16)(17)(18)(19)(20)(21)(22). As expected, both GST-CypA and GST-Domain I, but not GST, capture fulllength NS5A-His (Fig.…”
Section: Ns5a Forms Dimers Directly Through Domain I Interactions-mentioning
confidence: 78%
“…NS5A is a nonstructural protein that has no defined role in the virus life cycle but is absolutely required for RNA replication (8 -10) and particle assembly (11)(12)(13)(14). It has also been shown to interact with a large number of host proteins including CypA (cyclophilin A) (15)(16)(17)(18)(19)(20)(21)(22). NS5A is peripherally anchored to membranes by an N-terminal amphipathic helix (23)(24)(25)(26)(27).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…Combination of IFN and cyclosporine A was clearly more effective in achieving SVR than IFN monotherapy, especially in subjects with HCV-1, high viral load, or both (Inoue et al, 2003). Chatterji et al (2010) demonstrated that full-length NS5A and cyclophilins A form a stable complex. Remarkably, the interaction of cyclophilin A and NS5A is conserved among genotypes, and cyclosporine A is able to prevent the interaction of cyclophilin A and NS5A in a dose-dependent manner .…”
Section: Cyclophilin Binding Moleculesmentioning
confidence: 96%